Aplastic anaemia and the hypocellular myelodysplastic syndrome: histomorphological, diagnostic, and prognostic features. Issue 11 (November 1985) - Fohlmeister, I; Fischer, R; Mödder, B; Rister, M; Schaefer, H E
Abstract : In a retrospective study of 111 patients with aplastic anaemia iliac crest biopsies were evaluated for the presence of morphological features statistically related to the evolution of the disease. Prognostic variables for a transition to acute non-lymphatic leukaemia were: cellular atypias of the three haemopoietic lineages, as observed in the myelodysplastic syndrome, and especially "micromegakaryocytes"; high numbers or irregular distribution of megakaryocytes, or both; and (slight) marrow fibrosis. Clinical variables did not influence these prognostic correlations. Prognosis in relation to death from bone marrow failure without leukaemia might well have been influenced by a strong plasma cell reaction, but this correlation was weakened by clinical factors. On the basis of this study aplastic anaemia can thus be subdivided morphologically into two disease entities--namely, hypocellular myelodysplastic syndrome with a 23-82% risk of acute non-lymphatic leukaemia developing within three years, depending on how many variables associated with acute non-lymphatic leukaemia are present, and non-dysplastic myelohypoplasia.